The role and place of health care institutions during the implementation of measures in the field of prevention and counteraction of domestic violence in Ukraine - Medvedska, Viktoriia; Sobol, Yevhen; Tanryverdiiev, Isa Musa Ohly; Krasnohor, Oleksandr; Zhuravlova, Zoria (Edelweiss Applied Science and Technology, 2025)
The purpose of the article is to analyze the regulatory and legal framework governing the activities of medical institutions in the field of preventing and combating domestic violence and to develop proposals for improving the powers of medical institutions in this area. During the study of this problem, general scientific and special methods of scientific knowledge were employed, namely: systemic-structural, which was used to analyze the actions of medical institutions in the event of identifying victims of domestic violence; comparative, which made it possible to outline the specifics of the behavior of medical institutions when identifying victims of domestic violence in foreign countries; formal-legal, which was used to analyze the content of current legislation and the practice of its application; and the method of legal interpretation, which clarified the content of relevant legal norms, including evaluative concepts used in the law. The article presents the results of a study on the role of medical institutions in implementing measures to prevent and combat domestic violence, reveals the principles of providing medical care to victims of domestic violence, and analyzes the response algorithm of medical workers upon identifying victims of domestic violence. The materials of the article are useful for scientists and practitioners involved in the issues of preventing and combating domestic violence, for planning and forecasting further scientific research, improving legislation on preventing and combating domestic violence, for teachers and students of higher education institutions, as well as for ordinary citizens.